B-Mode ultrasound assessment of intima-media thickness of common carotid, internal carotid, brachial, femoral arteries and abdominal aorta in patients with cardiovascular risk factor - Koç, Ayşe Selcan; Peköz, Burçak Çakır (Journal of Surgery and Medicine, 2018)
Aim: The aim of the present study was to assess the association between common carotid intima-media thickness (IMT) and vascular IMT values measured from different anatomic regions. Methods: We prospectively included 256 patients. The IMT values of the common carotid and internal carotid, brachial and femoral artery and abdominal aorta were measured by B-mode ultrasound (CC-IMT, IC-IMT, B-IMT, F-IMT and A-IMT). Patients were divided into two groups as increased and normal CC-IMT. Results: Increased CC-IMT was detected in 55 of 256 patients (21.5%). All IMT variables showed a positive correlation with CC-IMT. Femoral IMT was independently associated with increased CC-IMT. In regression model, each 0.1 mm increase in F-IMT increased the risk of increased CC-IMT by 70.2%. When F-IMT value 1.1 mm was accepted as a cut-off value for the prediction of increased CC-IMT, sensitivity and specificity were 96.4% and 90%, respectively. In ROC curve analyses, the area under curve was calculated as 0.936. Conclusions: Another vascular IMT location presenting increased CC-IMT best is F-IMT. The limit value for increased F-IMT >1.1mm may be used in practice. The CC-IMT measurement is closely and positively associated with all other vascular IMT measurements.